Active tumor-targeting luminescent gold clusters with efficient urinary excretion. Issue 59 (29th June 2016) - Wang, Xiaojuan; He, Hua; Wang, Yanan; Wang, Junying; Sun, Xing; Xu, Hai; Nau, Werner M.; Zhang, Xiaodong; Huang, Fang
Abstract : Novel active tumor targeting fluorescent gold nanoclusters are synthesized through a facile method. Abstract : We present novel active targeting luminescent gold nanoclusters (AuNCs), which are prepared through a one-pot procedure by using a pentapeptide (CRGDS) for stabilization and tumor recognition. CRGDS–AuNCs exhibit a high tumor-specific retention with an exceptionally high tumor-to-liver uptake ratio of 9.3. Their small hydrodynamic diameter and zwitterionic surface facilitate urinary excretion, which reaches 82% within 24 h after injection.